5.1.43 Problems 4201 to 4300

Table 5.85: First order ode

#

ODE

Mathematica

Maple

9038

\[ {}{y^{\prime }}^{3} = \frac {y^{2}}{x} \]

9039

\[ {}{y^{\prime }}^{2} = \frac {1}{x y} \]

9040

\[ {}{y^{\prime }}^{2} = \frac {1}{x y^{3}} \]

9041

\[ {}{y^{\prime }}^{2} = \frac {1}{x^{2} y^{3}} \]

9042

\[ {}{y^{\prime }}^{4} = \frac {1}{x y^{3}} \]

9043

\[ {}{y^{\prime }}^{2} = \frac {1}{y^{4} x^{3}} \]

9044

\[ {}y^{\prime } = \sqrt {1+6 x +y} \]

9045

\[ {}y^{\prime } = \left (1+6 x +y\right )^{{1}/{3}} \]

9046

\[ {}y^{\prime } = \left (1+6 x +y\right )^{{1}/{4}} \]

9047

\[ {}y^{\prime } = \left (a +b x +y\right )^{4} \]

9048

\[ {}y^{\prime } = \left (\pi +x +7 y\right )^{{7}/{2}} \]

9049

\[ {}y^{\prime } = \left (a +b x +c y\right )^{6} \]

9050

\[ {}y^{\prime } = {\mathrm e}^{x +y} \]

9051

\[ {}y^{\prime } = 10+{\mathrm e}^{x +y} \]

9052

\[ {}y^{\prime } = 10 \,{\mathrm e}^{x +y}+x^{2} \]

9053

\[ {}y^{\prime } = x \,{\mathrm e}^{x +y}+\sin \left (x \right ) \]

9054

\[ {}y^{\prime } = 5 \,{\mathrm e}^{x^{2}+20 y}+\sin \left (x \right ) \]

9058

\[ {}t y^{\prime }+y = t \]

9059

\[ {}y^{\prime }-t y = 0 \]

9060

\[ {}t y^{\prime }+y = 0 \]

9061

\[ {}t y^{\prime }+y = 0 \]

9062

\[ {}t y^{\prime }+y = 0 \]

9063

\[ {}t y^{\prime }+y = 0 \]

9064

\[ {}t y^{\prime }+y = 0 \]

9065

\[ {}t y^{\prime }+y = \sin \left (t \right ) \]

9066

\[ {}t y^{\prime }+y = t \]

9067

\[ {}t y^{\prime }+y = t \]

9068

\[ {}y^{\prime }+t^{2} y = 0 \]

9069

\[ {}\left (a t +1\right ) y^{\prime }+y = t \]

9070

\[ {}y^{\prime }+\left (a t +b t \right ) y = 0 \]

9071

\[ {}y^{\prime }+\left (a t +b t \right ) y = 0 \]

9130

\[ {}y^{\prime } = \left (x +y\right )^{4} \]

9162

\[ {}y^{\prime }+y \cot \left (x \right ) = 2 \cos \left (x \right ) \]

9163

\[ {}2 x y^{2}-y+\left (y^{2}+x +y\right ) y^{\prime } = 0 \]

9164

\[ {}y^{\prime } = x -y^{2} \]

9171

\[ {}y^{\prime } = y^{{1}/{3}} \]

10015

\[ {}y^{\prime }-\frac {1}{\sqrt {\operatorname {a4} \,x^{4}+\operatorname {a3} \,x^{3}+\operatorname {a2} \,x^{2}+\operatorname {a1} x +\operatorname {a0}}} = 0 \]

10016

\[ {}y^{\prime }+a y-c \,{\mathrm e}^{b x} = 0 \]

10017

\[ {}y^{\prime }+a y-b \sin \left (c x \right ) = 0 \]

10018

\[ {}y^{\prime }+2 x y-x \,{\mathrm e}^{-x^{2}} = 0 \]

10019

\[ {}y^{\prime }+y \cos \left (x \right )-{\mathrm e}^{2 x} = 0 \]

10020

\[ {}y^{\prime }+y \cos \left (x \right )-\frac {\sin \left (2 x \right )}{2} = 0 \]

10021

\[ {}y^{\prime }+y \cos \left (x \right )-{\mathrm e}^{-\sin \left (x \right )} = 0 \]

10022

\[ {}y^{\prime }+y \tan \left (x \right )-\sin \left (2 x \right ) = 0 \]

10023

\[ {}y^{\prime }-\left (a +\cos \left (\ln \left (x \right )\right )+\sin \left (\ln \left (x \right )\right )\right ) y = 0 \]

10024

\[ {}y^{\prime }+f^{\prime }\left (x \right ) y-f \left (x \right ) f^{\prime }\left (x \right ) = 0 \]

10025

\[ {}y^{\prime }+f \left (x \right ) y-g \left (x \right ) = 0 \]

10026

\[ {}y^{\prime }+y^{2}-1 = 0 \]

10027

\[ {}y^{\prime }+y^{2}-a x -b = 0 \]

10028

\[ {}y^{\prime }+y^{2}+a \,x^{m} = 0 \]

10029

\[ {}y^{\prime }+y^{2}-2 x^{2} y+x^{4}-2 x -1 = 0 \]

10030

\[ {}y^{\prime }+y^{2}+\left (x y-1\right ) f \left (x \right ) = 0 \]

10031

\[ {}y^{\prime }-y^{2}-3 y+4 = 0 \]

10032

\[ {}y^{\prime }-y^{2}-x y-x +1 = 0 \]

10033

\[ {}y^{\prime }-\left (x +y\right )^{2} = 0 \]

10034

\[ {}y^{\prime }-y^{2}+\left (x^{2}+1\right ) y-2 x = 0 \]

10035

\[ {}y^{\prime }-y^{2}+y \sin \left (x \right )-\cos \left (x \right ) = 0 \]

10036

\[ {}y^{\prime }-y^{2}-y \sin \left (2 x \right )-\cos \left (2 x \right ) = 0 \]

10037

\[ {}y^{\prime }+y^{2} a -b = 0 \]

10038

\[ {}y^{\prime }+y^{2} a -b \,x^{\nu } = 0 \]

10039

\[ {}y^{\prime }+y^{2} a -b \,x^{2 \nu }-c \,x^{\nu -1} = 0 \]

10040

\[ {}y^{\prime }-\left (y A -a \right ) \left (B y-b \right ) = 0 \]

10041

\[ {}y^{\prime }+a y \left (y-x \right )-1 = 0 \]

10042

\[ {}y^{\prime }+x y^{2}-x^{3} y-2 x = 0 \]

10043

\[ {}y^{\prime }-x y^{2}-3 x y = 0 \]

10044

\[ {}y^{\prime }+x^{-a -1} y^{2}-x^{a} = 0 \]

10045

\[ {}y^{\prime }-a \,x^{n} \left (1+y^{2}\right ) = 0 \]

10046

\[ {}y^{\prime }+y^{2} \sin \left (x \right )-\frac {2 \sin \left (x \right )}{\cos \left (x \right )^{2}} = 0 \]

10047

\[ {}y^{\prime }-\frac {y^{2} f^{\prime }\left (x \right )}{g \left (x \right )}+\frac {g^{\prime }\left (x \right )}{f \left (x \right )} = 0 \]

10048

\[ {}y^{\prime }+f \left (x \right ) y^{2}+g \left (x \right ) y = 0 \]

10049

\[ {}y^{\prime }+f \left (x \right ) \left (y^{2}+2 a y+b \right ) = 0 \]

10050

\[ {}y^{\prime }+y^{3}+a y^{2} x = 0 \]

10051

\[ {}y^{\prime }-y^{3}-a \,{\mathrm e}^{x} y^{2} = 0 \]

10052

\[ {}y^{\prime }-a y^{3}-\frac {b}{x^{{3}/{2}}} = 0 \]

10053

\[ {}y^{\prime }-\operatorname {a3} y^{3}-\operatorname {a2} y^{2}-\operatorname {a1} y-\operatorname {a0} = 0 \]

10054

\[ {}y^{\prime }+3 a y^{3}+6 a y^{2} x = 0 \]

10055

\[ {}y^{\prime }+a x y^{3}+b y^{2} = 0 \]

10056

\[ {}y^{\prime }-x \left (x +2\right ) y^{3}-\left (x +3\right ) y^{2} = 0 \]

10057

\[ {}y^{\prime }+\left (4 x \,a^{2}+3 a \,x^{2}+b \right ) y^{3}+3 x y^{2} = 0 \]

10058

\[ {}y^{\prime }+2 a \,x^{3} y^{3}+2 x y = 0 \]

10059

\[ {}y^{\prime }+2 \left (a^{2} x^{3}-b^{2} x \right ) y^{3}+3 b y^{2} = 0 \]

10060

\[ {}y^{\prime }-x^{a} y^{3}+3 y^{2}-x^{-a} y-x^{-2 a}+a \,x^{-a -1} = 0 \]

10061

\[ {}y^{\prime }-a \left (x^{n}-x \right ) y^{3}-y^{2} = 0 \]

10062

\[ {}y^{\prime }-\left (a \,x^{n}+b x \right ) y^{3}-c y^{2} = 0 \]

10064

\[ {}y^{\prime }-f_{3} \left (x \right ) y^{3}-f_{2} \left (x \right ) y^{2}-f_{1} \left (x \right ) y-f_{0} \left (x \right ) = 0 \]

10065

\[ {}y^{\prime }-\left (y-f \left (x \right )\right ) \left (y-g \left (x \right )\right ) \left (y-\frac {f \left (x \right ) a +b g \left (x \right )}{a +b}\right ) h \left (x \right )-\frac {f^{\prime }\left (x \right ) \left (y-g \left (x \right )\right )}{f \left (x \right )-g \left (x \right )}-\frac {g^{\prime }\left (x \right ) \left (y-f \left (x \right )\right )}{g \left (x \right )-f \left (x \right )} = 0 \]

10066

\[ {}y^{\prime }-a y^{n}-b \,x^{\frac {n}{1-n}} = 0 \]

10067

\[ {}y^{\prime }-f \left (x \right )^{1-n} g^{\prime }\left (x \right ) y^{n} \left (a g \left (x \right )+b \right )^{-n}-\frac {f^{\prime }\left (x \right ) y}{f \left (x \right )}-f \left (x \right ) g^{\prime }\left (x \right ) = 0 \]

10068

\[ {}y^{\prime }-a^{n} f \left (x \right )^{1-n} g^{\prime }\left (x \right ) y^{n}-\frac {f^{\prime }\left (x \right ) y}{f \left (x \right )}-f \left (x \right ) g^{\prime }\left (x \right ) = 0 \]

10069

\[ {}y^{\prime }-f \left (x \right ) y^{n}-g \left (x \right ) y-h \left (x \right ) = 0 \]

10070

\[ {}y^{\prime }-f \left (x \right ) y^{a}-g \left (x \right ) y^{b} = 0 \]

10071

\[ {}y^{\prime }-\sqrt {{| y|}} = 0 \]

10072

\[ {}y^{\prime }-a \sqrt {y}-b x = 0 \]

10073

\[ {}y^{\prime }-a \sqrt {1+y^{2}}-b = 0 \]

10074

\[ {}y^{\prime }-\frac {\sqrt {y^{2}-1}}{\sqrt {x^{2}-1}} = 0 \]

10075

\[ {}y^{\prime }-\frac {\sqrt {x^{2}-1}}{\sqrt {y^{2}-1}} = 0 \]

10076

\[ {}y^{\prime }-\frac {y-x^{2} \sqrt {x^{2}-y^{2}}}{x y \sqrt {x^{2}-y^{2}}+x} = 0 \]

10077

\[ {}y^{\prime }-\frac {1+y^{2}}{{| y+\sqrt {1+y}|} \left (1+x \right )^{{3}/{2}}} = 0 \]

10078

\[ {}y^{\prime }-\sqrt {\frac {y^{2} a +b y+c}{a \,x^{2}+b x +c}} = 0 \]

10079

\[ {}y^{\prime }-\sqrt {\frac {y^{3}+1}{x^{3}+1}} = 0 \]